Community Oriented-Rural Tourism Development Model - Thakuri, Indra Bahadur Malla; Nepal, Govind (American Economic & Social Review, 2018)
Nepal is endowed with the majestic Himalayan ranges, including Mt. Everest, which is 8848 m, is the world’s highest mountain peak. Nepal is renowned world-wide as a prime tourist destination due to its unparalleled natural beauty; diverse bio-diversity; ethnic, lingual and social diversity; and historical and cultural wealth. There are many lakes, rivers, mountainous areas, museums, national parks, historical places, greenery forests, cultural heritages which become attractions to the tourists in Nepal. Rural setting is one of the most potential areas to promote the rural tourism where tourists can have opportunity to observe the rural setting, culture, life-style, social relationship, hospitality etc of rural people in Nepal. So, the study has developed the community oriented rural tourism development model covering the stages of development. The study was conducted in Lamjung, Tanahu and Nawalparasi districts among the home-stay operators, tourist experts and other tourism related stakeholders. In-depth interview was done with the respondents to collect their opinion about the best model of rural tourism. The study has developed the Community Oriented Rural Tourism Development Model (CO-RTDM) which has explained the seven stages of development.